An exploration and comparison of food and drink availability in homes in a sample of families of White and Pakistani origin within the UK. Issue 7 (10th March 2014) - Bryant, Maria; Sahota, Pinki; Santorelli, Gillian; Hill, Andrew
Abstract: Objective: Knowledge of the types and quantities of foods and drinks available in family homes supports the development of targeted intervention programmes for obesity prevention or management, or for overall diet improvement. In the UK, contemporary data on foods that are available within family homes are lacking. The present study aimed to explore home food and drink availability in UK homes. Design: An exploratory study using researcher-conducted home food availability inventories, measuring all foods and drinks within the categories of fruits, vegetables, snack foods and beverages. Setting: Bradford, a town in the north of the UK. Subjects: Opportunistic sample of mixed ethnicity families with infants approximately 18 months old from the Born in Bradford birth cohort. Results: All homes had at least one type of fruit, vegetable and snack available. Fresh fruits commonly available were oranges, bananas, apples, satsumas and grapes. Commonly available fresh vegetables included potatoes, cucumber, tomatoes and carrots. The single greatest non-fresh fruit available in homes was raisins. Non-fresh vegetables contributing the most were frozen mixed vegetables, tinned tomatoes and tinned peas. Ethnic differences were found for the availability of fresh fruits and sugar-sweetened beverages, which were both found in higher amounts in Pakistani homes compared with White homes. Conclusions: These data contribute to international data on availability and provide an insight into food availability within family homes in the UK. They have also supported a needs assessment of the development of a culturally specific obesity prevention intervention in which fruits and vegetables and sugar-sweetened beverages are targeted.